2014
DOI: 10.1007/s00894-014-2268-7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of β-cyclodextrin as catalyst with acetophenone in asymmetric reaction: a theoretical survey

Abstract: The asymmetric reduction of acetophenone with sodium borohydride in the presence of β-cyclodextrin (β-CD) as catalyst can improve selectivity and yield. The interaction between acetophenone and β-CD plays an important role for the reduction of acetophenone. This work studies the reaction of acetophenone in the presence of β-CD using density functional theory (DFT) method. Energy is investigated to find out the lowest energy of two possible complexation models. The geometrical structure confirms that acetopheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Moreover, it has been shown that the optical yields of the resulting alcohols also depend on the reaction temperature: ee significantly increased with a decrease of the reaction temperature. Wan et al [39] studied the interaction between acetophenone and β-CD in the complex and confirmed that acetophenone inserts into the cavity mainly from the secondary hydroxyls side. The results of the hydrogen bonds analysis confirmed the donor-acceptor interactions in the complex; while 13 C NMR results showed that the active site concentrates on the carbon atom of the carbonyl group.…”
Section: Methodsmentioning
confidence: 94%
“…Moreover, it has been shown that the optical yields of the resulting alcohols also depend on the reaction temperature: ee significantly increased with a decrease of the reaction temperature. Wan et al [39] studied the interaction between acetophenone and β-CD in the complex and confirmed that acetophenone inserts into the cavity mainly from the secondary hydroxyls side. The results of the hydrogen bonds analysis confirmed the donor-acceptor interactions in the complex; while 13 C NMR results showed that the active site concentrates on the carbon atom of the carbonyl group.…”
Section: Methodsmentioning
confidence: 94%
“…Similarly, the asymmetric reductions of prochiral ketones were also reported in different enantiometric excesses using modified cyclodextrins as supramolecular catalysts [ 53 , 54 ].…”
Section: Application Of Cyclodextrin In Asymmetric Reactionmentioning
confidence: 99%